International retrospective cohort study of neural tube defects in relation to folic acid recommendations: are the recommendations working?. Issue 7491 (18th February 2005) - Botto, Lorenzo D; Lisi, Alessandra; Robert-Gnansia, Elisabeth; Erickson, J David; Vollset, Stein Emil; Mastroiacovo, Pierpaolo; Botting, Beverley; Cocchi, Guido; de Vigan, Catherine; de Walle, Hermien; Feijoo, Maria; Irgens, Lorentz M; et al.
Abstract: Objectives To evaluate the effectiveness of policies and recommendations on folic acid aimed at reducing the occurrence of neural tube defects. Design Retrospective cohort study of births monitored by birth defect registries. Setting 13 birth defects registries monitoring rates of neural tube defects from 1988 to 1998 in Norway, Finland, Northern Netherlands, England and Wales, Ireland, France (Paris, Strasbourg, and Central East), Hungary, Italy (Emilia Romagna and Campania), Portugal, and Israel. Cases of neural tube defects were ascertained among liveborn infants, stillbirths, and pregnancy terminations (where legal). Policies and recommendations were ascertained by interview and literature review. Main outcome measures Incidences and trends in rates of neural tube defects before and after 1992 (the year of the first recommendations) and before and after the year of local recommendations (when applicable). Results The issuing of recommendations on folic acid was followed by no detectable improvement in the trends of incidence of neural tube defects. Conclusions Recommendations alone did not seem to influence trends in neural tube defects up to six years after the confirmation of the effectiveness of folic acid in clinical trials. New cases of neural tube defects preventable by folic acid continue to accumulate. A reasonable strategy would be to quickly integrate food fortification with fuller implementation of recommendations on supplements.